2020
DOI: 10.34067/kid.0001832020
|View full text |Cite
|
Sign up to set email alerts
|

The Geometry of Arteriovenous Fistulas Using Endothelial Nitric Oxide Synthase Mouse Models

Abstract: BackgroundArteriovenous fistula (AVF) maturation failure is a significant clinical problem in the hemodialysis population. Geometric parameters of human AVFs were associated with AVF development, but causative studies are lacking. We characterized mouse AVF geometry using endothelial nitric oxide synthase (NOS3) mouse models.MethodsCarotid-jugular AVFs were created in NOS3 overexpression (OE), knockout (KO), and wild-type (WT) mice. At 7 and 21 days postcreation, black-blood magnetic resonance images of AVFs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The linear correlation between the following was also analyzed because we found them to be significant in a carotid-jugular mouse AVF model ( Falzon et al, 2020 ): maximum venous CSA and average venous CSA, the minimum venous CSA and maximum A-V distance, tortuosity and maximum A-V distance, vein length at the maximum A-V distance and the maximum A-V distance, the nonplanarity angle magnitude and the maximum A-V distance, and the nonplanarity angle and the vein length at the maximum A-V distance. However, none of the correlations were significant in the femoral rat AVF model ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The linear correlation between the following was also analyzed because we found them to be significant in a carotid-jugular mouse AVF model ( Falzon et al, 2020 ): maximum venous CSA and average venous CSA, the minimum venous CSA and maximum A-V distance, tortuosity and maximum A-V distance, vein length at the maximum A-V distance and the maximum A-V distance, the nonplanarity angle magnitude and the maximum A-V distance, and the nonplanarity angle and the vein length at the maximum A-V distance. However, none of the correlations were significant in the femoral rat AVF model ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Centerline-based approaches for geometric analysis of blood vessels have been reported in the literature ( Kamenskiy et al, 2012 ; Aristokleous et al, 2018 ; Corbett et al, 2018 ). Therefore, our group used this approach to characterize AVFs in human ( He et al, 2021 ) and mouse ( Falzon et al, 2020 ), and here we used it on rats. Previously we reported that carotid jugular AVFs created in NOS3 overexpression mice had bigger CSA and flow than AVFs created in NOS3 knockout mice and wild-type mice ( Pike et al, 2019 ; Falzon et al, 2020 ), but AVFs in three mouse strains had similar anastomosis angle, tortuosity, and nonplanarity angle ( Falzon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations